Enhancement of antenna's bandwidth with the size modification on Barium Strontium Titanate elements - Wee, Fwen Hoon; Mohd Fareq, Abdul Malek, Dr.; Khairudi, Mohd Juni; Mohd Iskandar, Mohd Saleh; Mohd Shaharom, Idris (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/